Lived experience of Argentine microbusiness growth : It is not what you do, but how you do it - Koskinen, Johanna (fi=Turun yliopisto|en=University of Turku|, 2018)
Company growth is one of the most widely studied topics in economic literature. Yet, there is still a lack of research on microbusiness growth in Argentina. The purpose of this thesis is to bring new knowledge on how Argentine microbusinesses grow and distinguish their main growth strategies using ethnographic methods. The theoretical background of this research includes literature on microbusiness growth and their growth strategies. Particularly important was to understand the stages of small business growth, the key variables affecting microbusiness growth and different growth strategies. The data for this ethnographic study was collected from six different companies during the fall of 2016 and spring of 2017, while I worked in Fide, a business incubator in Córdoba, Argentina. Four businesses were chosen from the business incubator Fide and two businesses were chosen outside the business incubator. My aim as a researcher was to build close relationships with the owners of these businesses in order to gather relevant and trustworthy information. The main research methods used were non-participant observations, participant observations and in-depth semi-structured interviews with a life-story approach. All information on the companies and interviews gathered were in Spanish and later translated to English. In general, the results on key variables affecting microbusiness growth appeared to be consistent with previous findings in literature. The results on entrepreneur characteristics additionally highlighted the importance of language skills and how entrepreneurs typically start primarily with their own savings. The findings on company attributes provided new insight into the difficulties entrepreneurs face with government financial support. The results on networks offered powerful evidence that being part of a government-funded startup program or a business incubator enhanced the possibilities of obtaining broad professional networks. Economic fluctuations and inflation were seen as the strongest macroeconomic factors constraining growth. Flexibility was the key to success and also needed in determining the best-suited growth strategy and in some cases a mixture of more than one strategy. This research provided an interesting insight on how digital platforms may offer microbusinesses in Argentina possibilities to expand more rapidly and profitably to customers globally. Future research should be done in determining whether digital platforms offer new opportunities for all developing countries.